Influence of the Retrocolic Versus Antecolic Route for Alimentary Tract Reconstruction on Delayed Gastric Emptying After Pancreatoduodenectomy: A Multicenter, Noninferiority Randomized Controlled Trial. Issue 6 (December 2021) - Toyama, Hirochika; Matsumoto, Ippei; Mizumoto, Takuya; Fujita, Hirofumi; Tsuchida, Shinobu; Kanbara, Yoshihiro; Kadowaki, Yoshihiko; Maeda, Hiromi; Okano, Keiichi; Fukuoka, Masato; Takase, Shiro; Shirakawa, Sachiyo; et al.
Abstract : Objective: This study aimed to determine whether retrocolic alimentary tract reconstruction is noninferior to antecolic reconstruction in terms of DGE incidence after pancreatoduodenectomy (PD) and investigated patients' postoperative nutritional status. Summary of Background Data: The influence of the route of alimentary tract reconstruction on DGE after PD is controversial. Methods: Patients from 9 participating institutions scheduled for PD were randomly allocated to the retrocolic or antecolic reconstruction groups. The primary outcome was incidence of DGE, defined according to the 2007 version of the International Study Group for Pancreatic Surgery definition. Noninferiority would be indicated if the incidence of DGE in the retrocolic group did not exceed that in the antecolic group by a margin of 10%. Patients' postoperative nutrition data were compared as secondary outcomes. Results: Total, 109 and 103 patients were allocated to the retrocolic and antecolic reconstruction group, respectively (n = 212). Baseline characteristics were similar between both groups. DGE occurred in 17 (15.6%) and 13 (12.6%) patients in the retrocolic and antecolic group, respectively (risk difference; 2.97%, 95% confidence interval; −6.3% to 12.6%, which exceeded the specified margin of 10%). There were no differences in the incidence of other postoperative complications and in the duration of hospitalization. Postoperative nutritional indices were similar between both groups. Conclusions: This trial could not demonstrate the noninferiority of retrocolic to antecolic alimentary tract reconstruction in terms of DGE incidence. The alimentary tract should not be reconstructed via the retrocolic route after PD, to prevent DGE.